Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan CV. Unit Clean Industry Pasuruan) - Mutiarafani Tri Renata; Muhammad Agus Salim; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the influence of Transformational Leadership Style, Work Motivation, and Work Discipline on Employee Performance in a study on CV employees. Pasuruan Clean Industry Unit. This type of research used is quantitative research with the method of distributing questionnaires. The sample in this study were 47 respondents and data processing used the SPSS processing program. This research has met the requirements of validity and reliability. Data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and adjusted R square test. The variables used in this study are Transformational Leadership Style, Work Motivation, and Work Discipline. The results of this study concluded that the variables of Transformational Leadership Style, Work Motivation, and Work Discipline have both a simultaneous and partial effect on employee performance. Keywords: Transformational Leadership Style, Work Motivation, and Work Discipline.